Significance of alumina in nanofluid technology - Farhana, K.; K., Kadirgama; M. M., Rahman; M. M., Noor; D., Ramasamy; M., Samykano; G., Najafi; Nor Azwadi, Che Sidik; F., Tarlochan (Springer, 2019)
Nanotechnology has emerged to be an essential aspect of science and technology. The growth of this field has been enormous specifically in the development of nanomaterials. Till date, numerous nanomaterials have been developed and designed to suit various applications from mechanical to biomedical. Among the developed nanomaterial, alumina (Al) has been subject of interest due to its notable chemical and physical properties. Specifically, in thermal properties, Al has been shown to have superior thermal conductivity, convective heat transfer coefficient and heat transfer coefficient properties. As such, Al has been utilized in different forms in various fields of applications and verified for its importance, significance and efficiency. Though it had shown outstanding results in the field engineering and sciences, their effect towards the environment and human health is yet to be explored extensively. The present paper aims to review the significance of Al nanoparticle addition in mono- and hybrid nanofluids. Also, this paper intends to provide the reader with an overview of the works that have been carried out using Al nanoparticles and their findings.